Analisis Strategi Manajemen Penerimaan Peserta Didik Baru di Madrasah Al-Irfan, Kesawon, Serang - Firman Maulana; Jaenudin Jaenudin; Muhaimin Muhaimin; Angga Abhar Maulana; Riki Gana Suyatna (UNIVERSITAS MARITIM AMNI SEMARANG, 2025)
This study aims to identify the planning, implementation, and evaluation processes in the admission of new students at MDTA AL IRFAN, including factors that support and inhibit the process. This study uses a qualitative approach with a case study method. Data were collected through interviews, observations, and documentation, then analyzed using data reduction techniques, data presentation, and drawing conclusions or verification. The results of the study revealed that the management of new student admissions at MDTA AL IRFAN has shown positive performance. This was achieved through structured planning, efficient implementation, and continuous evaluation. Factors such as visionary leadership, collaboration with external parties, and community support are important aspects in the success of new student admissions. However, obstacles such as limited resources and the dynamics of changes in the external environment need to be addressed strategically so that MDTA AL IRFAN can continue to develop as an excellent Islamic educational institution that is in demand by the community.